Political Economy of Arab Revolutions: analysis and prospects for North-African Countries - (:unkn) unknown (My University, 2012)
Several similarities explain the spread of the Arab revolutionary process : the polarization of economies to limited sectors, a rentier-based management of resources, very low employment rates and extremely high rates of skilled migration. Finally, a similar external pact with the Western powers, and an inner pact between elites that have both imploded. This article suggests new directions for these economies that would combine regional integration and a catch-up strategy via service activities.
Keywords: African Research